2011
DOI: 10.1111/j.1365-2826.2011.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1Receptor Blockage Potentiates AMPA-Stimulated Luteinising Hormone Release in the Goldfish

Abstract: Previous microarray analyses of the goldfish hypothalamus led us to hypothesise that dopamine could potentially inhibit the excitatory effects of glutamate on luteinising hormone (LH). Post-spawning female goldfish were pre-treated (-4.5 h) with either saline (C; control), SCH 23390 (S; D(1) -receptor antagonist) or sulpiride (L; D(2) -receptor antagonist), followed by an i.p. injection, at -0.5 h, of saline or the glutamate agonist AMPA (A, SA or LA). Blood, hypothalamus and telencephalon tissues were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Previous studies have shown that intraperitoneal injections of male goldfish with either monosodium glutamate (MSG) (Sloley et al, 1992) or NMDA (Trudeau et al, 2000b) or AMPA (Trudeau et al, 2000b; Popesku et al, 2011) rapidly induces LH release. Furthermore, in rainbow trout it has been shown that the LH response to NMDA is blocked by APV or a GnRH receptor antagonist, indicating that glutamate modulates LH release through stimulation of GnRH (Flett et al, 1994), similar to the situation in mammalian models (Kocsis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that intraperitoneal injections of male goldfish with either monosodium glutamate (MSG) (Sloley et al, 1992) or NMDA (Trudeau et al, 2000b) or AMPA (Trudeau et al, 2000b; Popesku et al, 2011) rapidly induces LH release. Furthermore, in rainbow trout it has been shown that the LH response to NMDA is blocked by APV or a GnRH receptor antagonist, indicating that glutamate modulates LH release through stimulation of GnRH (Flett et al, 1994), similar to the situation in mammalian models (Kocsis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The POA controls the release of LH (Peter et al, 1990; Chang et al, 2000; Trudeau et al, 2000a,b) via a signaling pathway involving dopamine (DA), which tonically inhibits both GnRH and LH release (Peter and Paulencu, 1980; Kah et al, 1987; Sloley et al, 1992; Popesku et al, 2011). Coupled to the GABAergic inputs this area receives from the ventral telencephali pars ventralis (Vv) (Martinoli et al, 1990; Trudeau et al, 2000b), the vPOA may be the site where DA suppression of GnRH is removed to allow increased GnRH levels to elicit LH release and subsequent spawning.…”
Section: Introductionmentioning
confidence: 99%
“…This is a meta-type analysis of published experiments involving treatments of goldfish with DA agonists (Popesku et al, 2010), antagonists (Popesku et al, 2011a), and after pharmacological depletion of DA (Popesku et al, 2008). The abbreviated Materials and Methods pertaining to the experiments are included here for completeness.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that, while published, the previous DA depletion studies offered only a cursory analysis of the microarray data in the context of neurotransmitter effects on gene expression and did not specifically address global dopaminergic control of transcriptional responses. Furthermore, we present novel transcriptomic data for specific DA antagonism for which the physiological response to these antagonists has been published (Popesku et al, 2011a), but for which microarray analysis was not performed at that time. We used this novel dataset to compare these DA antagonism responses to agonist and DA depletion responses to improve identification of DA-regulated transcripts in the hypothalamus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation